What is Cochlearia venusta (Cruciferae)? - German, Dmitry A. (Phytotaxa, 2017)
Available material on the improperly known Cruciferae (Brassicaceae) species, Cochlearia venusta (Pseudosempervivum venustum), is revised and identified. The taxon is found to be conspecific with the eastern Anatolian endemic Noccaea bornmuelleri, previously long known as Thlaspi bornmuelleri (based on Syrenopsis bornmuelleri). The 10-years younger S. bornmuelleri is reduced to synonymy of C. venusta and a combination Noccaea venusta is validated. Original material of both names is briefly discussed; a lectotype (instead of holotype) is recognized for S. bornmuelleri and that is designated for C. venusta.